PERSUASIVE LANGUAGE STRATEGIES IN ENGLISH ISLAMIC COMMUNICATION: A LIBRARY STUDY ON DA’WAH MESSAGES IN DIGITAL MEDIA - Maulidah, Idah; Awliya, Rirry Nissa (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Digital media has fundamentally transformed the landscape of Islamic communication, enabling Muslim scholars, preachers, and communities to disseminate da’wah messages across geographical and cultural boundaries with unprecedented reach. Within this evolving communicative environment, the use of English as a vehicular language has gained considerable traction, particularly in reaching Muslim minorities in Western countries and non-Arabic-speaking communities worldwide. This study examines the persuasive language strategies employed in English-medium da’wah messages distributed through various digital platforms, including social media channels, online lectures, podcasts, and institutional websites. Drawing upon a systematic library study methodology, the research analyzes theoretical frameworks from rhetorical theory, discourse analysis, and Islamic communication studies to understand how contemporary Muslim communicators construct persuasive appeals. The objectives of the present investigation are threefold: to identify the dominant persuasive language strategies deployed in digital da’wah content in English, to examine how these strategies align with classical Islamic rhetorical traditions such as hikmah, maw’izah, and mujadalah, and to evaluate the effectiveness of these communicative approaches in contemporary digital contexts. The methodological approach adopted in this study involves the systematic collection, review, and critical analysis of published scholarly works, including books, accredited national journals, and internationally reputed academic journals published within the past three to five years. Findings reveal that digital da’wah practitioners employ a sophisticated amalgamation of Aristotelian appeals—ethos, pathos, and logos—alongside distinctively Islamic rhetorical conventions, constructing messages that are simultaneously persuasive, culturally sensitive, and spiritually grounded. The research further identifies narrative framing, emotional resonance, evidence-based argumentation, and interpersonal address as recurrent strategic features in high-engagement da’wah content. These findings carry significant implications for Islamic communication practitioners, educators, and scholars concerned with the effective propagation of Islamic values in the digital age